2017
DOI: 10.1016/j.apergo.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent audio-visual feedback for supporting drivers at intersections: A study using two linked driving simulators

Abstract: A large portion of road traffic crashes occur at intersections for the reason that drivers lack necessary visual information. This research examined the effects of an audio-visual display that provides real-time sonification and visualization of the speed and direction of another car approaching the crossroads on an intersecting road. The location of red blinking lights (left vs. right on the speedometer) and the lateral input direction of beeps (left vs. right ear in headphones) corresponded to the direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…From a more applied point of view, our results could prove useful when designing adaptive driver assistance systems (ADAS) for use at intersections. While the majority of the ADAS tested so far provided the drivers with cues related to the environment (e.g., the speed of approaching vehicles; Houtenbos et al, 2017), more powerful visual enhancements, i.e., related to the state of the agent-environment system, could benefit the driver. We already tested the usefulness of this type of visual enhancements in the context of landing an airplane (Huet, Jacobs, Camachon, Goulon & Montagne, 2009;Huet, Jacobs, Camachon, Missenard, Gray & Montagne, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…From a more applied point of view, our results could prove useful when designing adaptive driver assistance systems (ADAS) for use at intersections. While the majority of the ADAS tested so far provided the drivers with cues related to the environment (e.g., the speed of approaching vehicles; Houtenbos et al, 2017), more powerful visual enhancements, i.e., related to the state of the agent-environment system, could benefit the driver. We already tested the usefulness of this type of visual enhancements in the context of landing an airplane (Huet, Jacobs, Camachon, Goulon & Montagne, 2009;Huet, Jacobs, Camachon, Missenard, Gray & Montagne, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Possible remedies to PTW-car crashes could be adjustments in road design (e.g., the presence of a left-turn lane), automated emergency braking for PTWs (Savino et al, 2016), and vehicle-to-vehicle communication technologies for providing warnings in advance (Houtenbos et al, 2017). Furthermore, we see an opportunity for our results to be used in risk awareness training programs (cf.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Schwalk et al (2015) provided dynamic directional vibrotactile cues via the driver seat, which participants rated as appropriate for TORs, whereas Telpaz et al (2015) provided seat vibrations that made drivers aware of surrounding traffic during automated driving. More generally, research in a variety of applications areas has demonstrated the effectiveness of visual, auditory, and vibrotactile directional cues regarding reaction times and situation awareness (Houtenbos et al, 2017;Prewett et al, 2012).…”
Section: Directional Warningsmentioning
confidence: 99%